A Diels–Alder reaction between cyanates and cyclopentadienone-derivatives – a new class of crosslinkable oligomers. Issue 6 (10th January 2019) - Grätz, S.; Komber, H.; Bauer, M.; Voit, B.
Abstract : A Diels–Alder reaction between cyclopentadienones and cyanates yields thermally crosslinkable oligomers, which combine high thermal resistance and high refractive indices. Abstract : This study elucidates a new class of crosslinkable oligomers by combining the facile processability and crosslinkability of cyanate esters with the high temperature and optical properties of polyphenylenes. The structure of the resulting oligomers is scrutinously investigated by NMR, UV/Vis and IR spectroscopy. Additionally, the polymerisation and crosslinking reaction kinetics are looked into. After crosslinking, the resins exhibit high thermal resistance in combination with transparency and a high refractive index.